Influence of fractional flow reserve on grafts patency: Systematic review and patient‐level meta‐analysis. Issue 3 (7th July 2021) - G. Toth, Gabor; Collet, Carlos; Langhoff Thuesen, Anne; Mizukami, Takuya; Casselman, Filip; Riber, Lars Peter; Van Praet, Frank; Junker, Anders; Nagumo, Sakura; De Bruyne, Bernard; Okkels Jensen, Lisette; Barbato, Emanuele
Abstract: Objective: To investigate the impact of invasive functional guidance for coronary artery bypass graft surgery (CABG) on graft failure. Background: Data on the impact of fractional flow reserve (FFR) in guiding CABG are still limited. Methods: Systematic review and individual patient data meta‐analysis were performed. Primary objective was the risk of graft failure, stratified by FFR. Risk estimates are reported as odds ratios (ORs) derived from the aggregated data using random‐effects models. Individual patient data were analyzed using mixed effect model to assess relationship between FFR and graft failure. This meta‐analysis is registered in PROSPERO (CRD42020180444). Results: Four prospective studies comprising 503 patients referred for CABG, with 1471 coronaries, assessed by FFR were included. Graft status was available for 1039 conduits at median of 12.0 [IQR 6.6; 12.0] months. Risk of graft failure was higher in vessels with preserved FFR (OR 5.74, 95% CI 1.71–19.29). Every 0.10 FFR units decrease in the coronaries was associated with 56% risk reduction of graft failure (OR 0.44, 95% CI 0.34 to 0.59). FFR cut‐off to predict graft failure was 0.79. Conclusion: Surgical grafting of coronaries with functionally nonsignificant stenoses was associated with higher risk of graft failure.